(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2024)
Self-microemulsifying drug delivery systems (SMEDDS) have emerged as a promising approach to enhance the oral bioavailability of poorly water-soluble drugs. SMEDDS is composed of an oil phase, surfactant, co-surfactant, and drug, which spontaneously form a fine oil-in-water microemulsion when exposed to gastrointestinal fluids. This microemulsion enhances drug solubilization and absorption by increasing the drug’s surface area and promoting rapid gastrointestinal epithelium permeation. The formulation of SMEDDS involves careful selection and optimization of components to achieve desired drug solubility, stability, and emulsification efficiency. SMEDDS offers numerous advantages, including improved drug bioavailability, reduced variability in pharmacokinetic parameters, and the potential for reduced dosing frequency. They can effectively deliver a wide range of drugs, including lipophilic and poorly water-soluble compounds. This review provides an overview of SMEDDS, its advantages, and disadvantages, drug delivery mechanism, formulation design, excipients used for formulation, and evaluation techniques as well as their potential applications in drug delivery.